The place of small and medium enterprises within the sustainable development framework - Irina Purcarea (Contemporary Economics, 2008)
Small enterprises make up for at least 95% of the enterprises in the European Community, and constitute an important source of employment. Sustainable development, on the other hand, involves each of us, individual or organization. It is a concept that should be embraced by each of us, by each enterprise no matter its size. Each company should clearly understand the concept and undertake the specific actions considering the fact that their impact will have certain effects that will echo in the future, therefore affecting future generations. The present research intends to gain an insight into the approach adopted by small and medium enterprises as concerning the sustainable development framework, with a focus on corporate social responsibility initiatives undertaken by SMEs.
Keywords: 330